Associated Factors of Self-Management in Type 2 Diabetes Mellitus at Community Health Center - Malini, Hema; Yeni, Fitra; Pratiwi, Cindy Ayu; Lenggogeni, Devia Putri (Jurusan Keperawatan FIKES UNSOED, 2020)
Patients with diabetes mellitus have difficulties in managing their disease. Most of patients with uncontrolled diabetes have HbA1c > 9%. This study aimed to determine the factors associated with self-management of type 2 diabetes mellitus patients with HbA1c> 9% in Public Health Center, Padang 2019. This study used a cross-sectional design. The sampling technique using a total sampling technique with a total sample of 79 respondents. This study used a questionnaire that consists of questionnaires; DKQ, DMSES, S4-MAD, and SDSCA-revised. Data were analyzed using the Pearson Product Moment Correlation test. This study showed, knowledge (mean= 10.89), self-efficacy (mean= 50.01), social support (mean= 52.27), and self-management (mean= 48.38 ). The factors associated with self-management of type 2 diabetes mellitus patients with HbA1c> 9%, are knowledge (p = 0.016), self-efficacy (p = 0.000), and social support (p = 0.001). The most dominant factor in self-management of diabetes patients is self-efficacy (p-value = 0.000), (r = 0.607), and (r2 = 0.3684). Based on the study, it is recommended for health workers to be able to increase their attention to type 2 patients diabetes mellitus patient who have HbA1c> 9% to improve their efficacy in self-management so that patients can control bloodÂ